Glucano como adjuvante para antigeno Escherichia coli K99 en conejos - Sanchez, L.=700 1 Martinez, S.; Fuentes, E.D.
(Es, En)
Ilus., 13 ref.
Keywords: ANTIGENO; CONEJO (ORYCTOLAGUS); ESCHERICHIA COLI; SACCHAROMYCES CEREVISIAE; CUBA